Estudos estruturais por difração de raios X de fosfolipases A2 em presença de íons com importância funcional - Borges, Rafael Junqueira [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Snakes from Bothrops genus are responsible for more than 90% of the ophidian accidents in Brazil. One of the main complications from this kind of accident is muscular necrosis, which is related to the action of phospholipases A2 and metalloproteases, two groups of enzymes found in the venom of these animals. Although this complication cannot be solved by serum therapy administration, a great number of studies have been performed with the attempt to know the pharmacological sites of these toxins aiming, in the future, the development of complementary treatments to serum therapy. This work proposes structural studies of bothropic phospholipases A2 (PLA2s) in the presence of ions relevant to their activity, using the X-ray crystallography technique. Recently, it was demonstrated ions, as manganese, calcium and others, interfere in the biological activity of the PLA2s. Particularly, Lys49-PLA2s in the presence of manganese ions have miotoxicity reduced. Asp49-PLA2s show catalytic activity dependent of calcium, although structural studies with a miotoxic Asp49-PLA2, BthTX-II, suggest a possible catalytic mechanism independent of calcium. Therefore, co-crystallization of BthTX-II in the presence of calcium ions and of PrTX-I in the presence of manganese ions were performed. Comparative structural studies among obtained results and others already published in the literature were performed aiming a better understanding of the structure-function relationship of these toxins. The BthTX-II with the presence of calcium do not show this ion in the loop of coordination of calcium, presence necessary to develop the catalyses. After comparison of this model with the native one, only one distortion was found, but no apparent relationship with the residues responsible for its activity. In the PrTX-I structure, regions candidates of manganese ions were also found... (Complete abstract click electronic access below)

Serpentes do gênero Bothrops são responsáveis por mais de 90% dos acidentes ofídicos que ocorrem no Brasil. Uma das principais complicações deste tipo de acidente é a necrose muscular, que está relacionada à ação de fosfolipases A2 e metaloproteases, dois grupos de enzimas presentes no veneno destes animais. Esta complicação não é contornada pela administração do soro antiofídico e, por isso, diversos trabalhos vêm sendo realizados na tentativa de se conhecer os sítios farmacológicos destas toxinas com o intuito de, no futuro, se desenvolver tratamentos complementares à soroterapia. Este projeto de pesquisa tem como objetivo o estudo estrutural de fosfolipases A2 (PLA2s) botrópicas em presença de íons relevantes para a atividade das mesmas, através da técnica de cristalografia de raios X. Recentemente, foi demonstrado que íons, tal como manganês, cálcio e outros interferem na atividade biológica de PLA2s. Particularmente, Lys49-PLA2s na presença de íons manganês têm a atividade miotóxica bastante reduzida. Já as Asp49-PLA2s apresentam atividade catalítica dependente de cálcio, contudo estudos estruturais recentes com uma proteína Asp49-PLA2 miotóxica (BthTX-II) sugerem um possível mecanismo miotóxico independente deste íon. Dessa forma, foi realizado a cocristalização da BthTX-II em presença de íons cálcio e a co-cristalização da PrTX-I em presença de íons manganês. Estudos comparativos entre os resultados obtidos e os já existentes na literatura foram realizados na tentativa de melhor compreender as relações estrutura-função destas toxinas. A estrutura da BthTX-II em presença de íons cálcio não possui esse íon no sítio de coordenação de cálcio, ligação necessária para realizar a catálise. Após comparação desse modelo com o nativo, foi encontrado apenas um desvio significativo, porém sem relação aparente... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Fosfolipase A2; Serpente - Veneno; Cristalografia de proteínas